The New *G29A and G1222A of HCRTR1, 5-HTTLPR of SLC6A4 Polymorphisms and Hypocretin-1, Serotonin Concentrations in Migraine Patients - Kowalska, Marta; Kapelusiak-Pielok, Magdalena; Grzelak, Teresa; Wypasek, Ewa; Kozubski, Wojciech; Dorszewska, Jolanta (Frontiers in Molecular Neuroscience, 2018)
Migraine is one of the most common primary headache disorders that affects 11% of the adult population. The disease is divided into two main clinical subtypes: migraine with aura (MA) and migraine without aura (MO). Both serotonergic and hypocretinergic systems are involved in the migraine pathomechanism. Polymorphisms in the serotonin transporter gene (SLC6A4) and the hypocretin receptor 1 gene (HCRTR1) may be risk factors for migraine development due to their ability to affect serotonin and hypocretin-1 concentrations. The aim of the study was to analyze, for the first time in the Polish population, the serotonin transporter linked polymorphic region (5-HTTLPR) in SLC6A4, G1222A (rs2271933) and the never before studied *G29A (rs41263963) polymorphisms in the HCRTR1 gene, as well as the serotonin and hypocretin-1 plasma concentrations in migraine patients (MA, MO) and control subjects. The study included 123 patients that were diagnosed with migraine and 123 control subjects. Methods such as PCR, HRMA and sequencing were used for genotyping, while serotonin was determined by HPLC/EC and hypocretin-1 by ELISA. No significant differences were observed in 5-HTTLPR frequencies. The A allele of HCRTR1 G1222A occurred more often in MO, while the GA genotype of HCRTR1 *G29A was more frequent among MA when compared to control group (p<0.05). The mean age of migraine onset in individuals with HCRTR1 *G29A was 18 years old for patients with MA and 26 years old for MO patients. The localization and type of HCRTR1 polymorphisms (G1222A - missense variant in exon 7, *G29A - 3’UTR variant) may predispose patients to the clinical subtype of migraine: MO or MA, respectively. In control subjects, the short allele of 5-HTTLPR tended to decrease the serotonin concentration, while the A allele of HCRTR1 G1222A decreased both serotonin and hypocretin-1 levels. Serotonin concentrations differed in terms of clinical features of migraine. The relation between genotypes of 5-HTTLPR, HCRTR1 G1222A, and serotonin concentrations may be disturbed in migraine. It seems that HCRTR1 *G29A is more strongly associated with regulating the serotonin in patients with MA than MO, and therefore may contribute to the early age of onset for migraine.